Is leukotriene B4 one of the keloid marker? a fibroblast keloid study - Yuli Kurniawati; Oki Suwarsa; A. Achadiyani; Sudigdo Adi (Dermatology Reports, 2019)
Keloid pathogenesis occurs due to the duration of prolonged inflammatory phase and increased production of various growth factors such as TGF-β1 which may cause increasing fibroblast proliferation and collagen synthesis. Existence of one of the chemical mediators released during inflammation, leukotriene B4 (LTB4), in keloid pathogenesis specifically in the phases of inflammation and proliferation, is still unclear. The purpose of the study is to analyze the levels of LTB4 in keloid. Methods: Fibroblast culture that was done by explanting keloid and normal skin of a keloid patient. Measurement of LTB4 on keloid and normal fibroblast was done by Elisa method. This experiment was run in triplicate. Statistical test was conducted by t test for the unpaired data and Anova test. The experiment was done at cell culture laboratory of Medical Faculty of Padjadjaran University Bandung. Levels of LTB4 in keloid fibroblast was higher than that of normal skin fibroblast (mean 23143.27 vs 18191.85 pg/ml; p<0.05). Conclusion, increased LTB4 levels in keloid fibroblast showed the existence of LTB4 role in the prolonged inflammatory process in keloid pathogenesis.